2019
DOI: 10.1016/j.ghir.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 and cardiovascular disease

Abstract: Atherosclerosis is an inflammatory arterial pathogenic condition, which leads to ischemic cardiovascular diseases, such as coronary artery disease and myocardial infarction, stroke, and peripheral arterial disease. Atherosclerosis is a multifactorial disorder and its pathophysiology is highly complex. Changes in expression of multiple genes coupled with environmental and lifestyle factors initiate cascades of adverse events involving multiple types of cells (e.g. vascular endothelial cells, smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 202 publications
(244 reference statements)
1
82
0
2
Order By: Relevance
“…Our working hypothesis is that IGF-1 induces replenishing of P20 cells via mitophagy-mediated clearance of mitochondria and suppressing of cell senescence. This hypothesis is consistent with literature data indicating prosurvival and mitogenic effects of IGF-1 [ 6 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our working hypothesis is that IGF-1 induces replenishing of P20 cells via mitophagy-mediated clearance of mitochondria and suppressing of cell senescence. This hypothesis is consistent with literature data indicating prosurvival and mitogenic effects of IGF-1 [ 6 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that either induction of cell senescence or interruption of autophagic signaling in vascular SMC promoted atherosclerosis and induced features of plaque vulnerability in a murine model [ 50 , 51 ]. We and others [ 40 , 41 , 52 ] have reported that IGF-1 exerts antiatherosclerotic effects in mice that are mediated (at least in part) by IGF-1 receptor-dependent SMC signaling [ 15 ]. The results of the current report suggest that the ability of IGF-1 to reduce cell senescence and activate autophagy in vascular SMC could be a novel mechanism(s) potentially contributing to IGF-1's antiatherosclerotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 has long been known to have a beneficial role in diabetes and cardiovascular disease (Higashi et al, 2019). Beta-cell IGF-1 overexpression protects from STZ-induced diabetes (George et al, 2002;Robertson et al, 2008) and exogenous IGF-1 protects NOD mice from developing type 1 diabetes, likely via effects on T cells (Bergerot et al, 1995;Kaino et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The studies presented above, while not exhaustive, serve as examples to highlight the diverse role of MDM2 as a central hub in the cardiovascular system. Most human cardiovascular diseases are associated with DNA damage due to oxidative stress (Jackson and Bartek, 2009;Shimizu et al, 2014;Uryga et al, 2016) and alteration of hormonal signals (Higashi et al, 2019). The DNA damage kinase ATM is an upstream regulator of MDM2, and it does modulate the endothelial function, playing a role in atherosclerosis and angiogenesis.…”
Section: Summary Of "Mdm2's Social Network" and The Cardiovascular Symentioning
confidence: 99%